2021
DOI: 10.21203/rs.3.rs-861720/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hitting The Bullseye: The Psychometric Properties of the Assessment of Burden of Chronic Conditions (ABCC)-Scale in The Netherlands

Abstract: Background Chronic conditions impose a major impact on quality of life and on healthcare. The Assessment of Burden of Chronic Conditions (ABCC-)tool was developed to improve experienced quality of care and quality of life by facilitating shared decision-making and self-management. It assesses the experienced burden of one or multiple conditions, and visualises and integrates the burden in daily care. However, its scale’s validity and reliability are yet unknown. The aim of this study is to evaluate whether th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The strength of the previous developed ABCC-tool with modules for asthma, COPD, DM2 and chronic heart failure is that it includes care on a physical, emotional and social level, and facilitates shared-decision making. Studying the effectiveness of the ABCC-tool, it showed that patient experienced quality of care and patient activation improves [ 21 , 24 , 48 ]. Therefore, it was deemed desirable to create an OA module for the ABCC-tool because comparable effects might be expected.…”
Section: Discussionmentioning
confidence: 99%
“…The strength of the previous developed ABCC-tool with modules for asthma, COPD, DM2 and chronic heart failure is that it includes care on a physical, emotional and social level, and facilitates shared-decision making. Studying the effectiveness of the ABCC-tool, it showed that patient experienced quality of care and patient activation improves [ 21 , 24 , 48 ]. Therefore, it was deemed desirable to create an OA module for the ABCC-tool because comparable effects might be expected.…”
Section: Discussionmentioning
confidence: 99%
“…The Assessment of Burden of Chronic Conditions (ABCC) tool includes a PROM of which the outcomes are visualised into a balloon chart for easy comprehension. The tool is developed to guide care conversations towards the personal experienced burden of someone with chronic obstructive pulmonary disease (COPD), asthma, type 2 diabetes mellitus (T2DM) and/or chronic heart failure (CHF) 6 7. The tool consists of a scale that validly and reliably measures a patient’s experienced burden (ie, the PROM), a visualisation of the outcomes of that scale (figure 1) and domain-specific treatment advice based on the outcome of the scale 6–8.…”
Section: Introductionmentioning
confidence: 99%
“…The tool is developed to guide care conversations towards the personal experienced burden of someone with chronic obstructive pulmonary disease (COPD), asthma, type 2 diabetes mellitus (T2DM) and/or chronic heart failure (CHF) 6 7. The tool consists of a scale that validly and reliably measures a patient’s experienced burden (ie, the PROM), a visualisation of the outcomes of that scale (figure 1) and domain-specific treatment advice based on the outcome of the scale 6–8. As such, the ABCC-tool enables HCP and patient to address the experienced burden and to formulate personalised goals for the domains of choice.…”
Section: Introductionmentioning
confidence: 99%